Physical chemistry evaluation of stability, spreadability, in vitro antioxidant, and photo-protective capacities of topical formulations containing Calendula officinalis L. leaf extract - Viviane Cecília Kessler Nunes Deuschle; Regis Augusto Norbert Deuschle; Mariana Rocha Bortoluzzi; Margareth Linde Athayde (Universidade de São Paulo, 2015)
Calendula is used widely in cosmetic formulations that present phenolic compounds in their chemical constitution. The objective of our research was to develop and evaluate the stability of topical formulations containing 5% hydro-ethanolic extract of calendula leaves, including spreadability, and in vitro photo-protective, and antioxidant capacity. To evaluate the stability, we used organoleptic characteristics, pH, and viscosity parameters. Antioxidant capacity was measured by the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, and the photo-protective capacity by SPF spectrophotometric measure. All formulations were stable. The calendula extract formulations in gel and cream showed no significant variations in pH, and the cream formulations presented lower viscosity variations than gel formulations. The spreadability of the gel formulations was superior to those in cream. The formulations also presented good antioxidant capacities and an FPS of around 1.75. In accordance with the results, the formulations can be used as antioxidants, but considering the low SPF obtained, calendula cannot be considered as a stand-alone sunscreen, yet may well be tested in future studies towards verifying enhancement of synthetic sunscreens.